N‐Substituted Hydrazones by Manganese‐Catalyzed Coupling of Alcohols with Hydrazine: Borrowing Hydrogen and Acceptorless Dehydrogenation in One System. Issue 8 (29th January 2018) - Das, Uttam Kumar; Ben‐David, Yehoshoa; Diskin‐Posner, Yael; Milstein, David
Abstract: An unprecedented one‐step synthesis of N‐substituted hydrazones by coupling of alcohols with hydrazine is reported. This partial hydrogen‐borrowing reaction is catalyzed by a new manganese pincer complex under mild reaction conditions, thus liberating water and dihydrogen as the only byproducts. Mechanistic insight, based on the observation of intermediates, is provided. Abstract : In the zone : An unprecedented one‐step synthesis of N‐substituted hydrazones by coupling of alcohols with hydrazine is reported. This partial hydrogen‐borrowing and acceptorless dehydrogenation reaction is catalyzed by a new manganese pincer complex under mild reaction conditions, and liberates water and dihydrogen as the only byproducts.